Water service valuation in tidal lowland agriculture - Yazid Muhammad, Shamsudin Mad Nasir, Abdul Rahim Khalid, Radam Alias, Muda Azizi (N/A, 2015)
Water service valuation in tidal lowland agriculture by Yazid Muhammad, Shamsudin Mad Nasir, Abdul Rahim Khalid, Radam Alias, Muda Azizi,